A new configuration of multi-wavelength Brillouin fiber laser - Harun, Sulaiman Wadi; Shirazi, Mohammadreza Rezazadeh; Ahmad, Harith (John Wiley & Sons, 2013)
A multi-wavelength laser is demonstrated using stimulated Brillouin scattering in a single-mode fiber with a feedback loop using two couplers and an optical circulator. This Brillouin fiber laser can operate at any wavelength depending on the Brillouin pump (BP) wavelength used. With a BP of 14 dBm, approximately 8 to 10 BFL lines are obtained in both forward and backward directions respectively with a line spacing of 0.16 nm. The use of the 99/1 coupler and 50/50 coupler gives the highest power and number of lines for the forward and backward outputs respectively. The maximum Stokes power obtained is approximately 8.0 dBm. The anti-Stokes lines are also obtained due to four wave mixing and bidirectional operation. The combination of forward and backward output can generate a larger number of lines with channel spacing of 0.08 nm. A graph is presented.